(untitled) (LACCEI, 2024)
One of the main problems that every newspaper publishing company has is returns, since a high rate of returns generates a significant decrease in profits. When analyzing the return rates of international and national newspapers, it was determined that the company under study has a rate of 24%, which is higher than that of the other newspapers analyzed, since the ideal would be below 16%. In previous research, the agile SCRUM methodology was applied and reduced newspaper returns by 15%. Likewise, by implementing the BPM methodology, they were able to reduce incomplete dispatches from 34% to 14%. Distribution is a key process in the publishing sector because, if products are properly distributed and optimal delivery is ensured, the company will be able to increase its sales and its rate of returns will be minimal. Therefore, this research seeks to create a management model to reduce this problem through the use of the 5S methodology, BPM and dashboard control, in order to efficiently manage the indicators and consequently maximize their profits. Therefore, by implementing the solution model, it was possible to reduce the rate of returns and improve the condition of the warehouse. Finally, it is recommended that companies have standardized processes and apply tools that facilitate the visualization of their data in real time.